Maternal Mortality and Scheme for a National Maternity Service (interim report) - Labour Party (Great Britain). Advisory Committee on Public Health. Sub-committee on Maternal Mortality
1929-11 1929 1920s 12 pages - 7 - The doctor called in by the midwife and the doctor in difficulties with his own case should have the power to summon the consultant. The Local Authority should pay the consultant's fee. Moreover, the obstetric specialist should be able to send if need be for specialists in other branches, i.e., pathologist, bacteriologist, etc., who could aid the patient. 25. (D) The anaesthetist The doctor should have power to send for another doctor to act as anaesthetist. 26. (E) The student (1) Pupil midwife. These students working in association with a training school should be carefully supervised as is the practice at present in the best schools. 27. (2) Medical student. No medical student should be allowed to deliver a woman in her home until he has delivered six cases under supervision in a hospital; and in every case a trained midwife should be present at the confinement. 28. (F) Sterilised outfits Sterilised outfits should be provided, and must be available at any hour as required. III. INSTITUTIONAL SERVICES 29. (A) Municipal hospitals for maternity cases can be either small separate units for these cases only or sections of general hospitals. The latter should be a means of meeting a long-felt want; the County Council hospitals under the 1929 Act can provide the needed number of maternity beds and bring the nursing and medical requirements up to the standard of the best voluntary hospitals. Adequate nursing staff both qualified and pupils, resident medical officers and consultants must be provided, with facilities for laboratory work, etc. 292/824/1/115